2021
DOI: 10.21203/rs.3.rs-138978/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The polyphenol/saponin-rich Rhus tripartita extract has an apoptotic effect on THP-1 cells through the PI3K/AKT/mTOR signaling pathway

Abstract: Background Hyperactivation of mechanistic target of rapamycin (mTOR) signaling pathway is involved in the regulation of cellular growth, proliferation, and more in general, is a common phenomenon in most types of cancers. Thus, natural substances targeting this pathway can be of great therapeutic potential in supporting the treatment of tumor patients. Rhus tripartita (Ucria) Grande is a plant growing in desertic areas which is traditionally used for the treatment of several diseases in Tunisia. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Therefore, this extract may be a useful candidate as a natural anti-cancer drug to support the treatment of acute monocytic leukemia. 31 Martino demonstrated that the polyphenol extract from Annurca apple selectively kills MDA-MB-231 triple breast cancer cells through RoS generation, sustained JnK activation and cell growth and survival inhibition. 5 Meanwhile, combined polyphenols or mixed with micronutrients have shown to be effective against multiple targets in cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this extract may be a useful candidate as a natural anti-cancer drug to support the treatment of acute monocytic leukemia. 31 Martino demonstrated that the polyphenol extract from Annurca apple selectively kills MDA-MB-231 triple breast cancer cells through RoS generation, sustained JnK activation and cell growth and survival inhibition. 5 Meanwhile, combined polyphenols or mixed with micronutrients have shown to be effective against multiple targets in cancer development and progression.…”
Section: Discussionmentioning
confidence: 99%